Mетоди оцінки та способи їх зниження господарських ризиків на підприємстві - Середа, І.В.; Яковенко, А.Т. (Культура народов Причерноморья, 2013)
В даній статті запропонована методика розробки рішень про мінімізацію ризиків, на
основі дослідження фінансової стійкості, платоспроможності, кредитоспроможності, банкрутства
на прикладі підприємства через розгляд спеціальних коефіцієнтів ліквідності (абсолютної, загальної,
поточної), фінансової незалежності та ін., які дозволять підприємству зменшити господарські ризики
на підприємстві. Ціль статті є: використовуючи матеріали наукових публікацій розглянути методи
мінімізації ризиків на підприємстві.
Ключові слова: ризики, коефіцієнти ефективність, підприємство В данной статье предложена методика разработки решений о минимизации рисков, на
основе исследования финансовой устойчивости, платежеспособности, кредитоспособности,
банкротства на примере предприятия через рассмотрение специальных коэффициентов ликвидности
(абсолютной, общей, текущей), финансовой независимости и др., которые позволят предприятию
уменьшить хозяйственные риски на предприятии. Цель статьи: используя материалы научных
публикаций рассмотреть методы минимизации рисков на предприятии.
Ключевые слова: риски, коэффициенты эффективность, предприятие Risk assessment is the most important part of overall risk management system. It is a process to
establish quantitative or qualitative way of magnitude (degree) ризику.
Object article is: using materials of scientific publications to consider ways to minimize the risks of the
enterprise.
In this paper we propose a method of developing solutions on risk minimization, on the basis of research of
financial stability, solvency, credit bankruptcy on the example of the company through a consideration of the
special liquidity ratios (absolute, total, current), financial independence and other, that allows the company to
reduce economic risks at the enterprise.
Risk assessment carried out on the example of «the Kingdom of flavors» through the study of factors, the
calculation of which is based on the existence of a certain correlation between the separate items of the balance
sheet. The study of financial stability, solvency and creditworthiness, bankruptcy of OJSC «the Kingdom of
flavors» through consideration of the special liquidity ratios of financial independence, etc proposes a
methodology for determination of the risk based approach Altman and Lemma Markov.
Key words: risk, the coefficients of efficiency, enterprise.